Kebijakan Migrasi yang Responsif terhadap Gender sebagai Alat Kebijakan Luar Negeri Spanyol di Wilayah Mediterania (2020-2024) - Septania, Aulia Surya; Riyanto, Sugeng (Universitas Cenderawasih, 2025)
This study examines Spain’s gender-responsive migration policy as a foreign policy tool between 2020 and 2024, with a focus on the Mediterranean region. Using qualitative methods, VOS viewer analysis, and the frameworks of foreign policy analysis, image theory, and soft power, the research analyses how Spain embeds feminist and human rights values into migration governance to enhance its international image and normative legitimacy. Findings show that Spain increasingly employs migration policy not only to regulate cross-border mobility but also to project itself as a democratic and progressive actor, thereby strengthening its soft power and role as a normative leader in Global North-South relations. Nonetheless, the study identifies a gap between symbolic commitments and practical implementation, hindered by institutional fragmentation, weak gender-sensitive infrastructure, and rising domestic resistance. Despite these obstacles, Spain’s gender-responsive migration diplomacy illustrates a significant model for ethical diplomacy, nation branding, and feminist foreign policy in a contested global order. KEYWORDS Foreign policy; Gender-responsive migration; Mediterranean; Soft power; Spain